2016
DOI: 10.1149/2.1171608jes
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Si3N4and TiN Nano-Particles Reinforced Electrodeposited Functional Ni-Fe Matrix Nanocomposite

Abstract: Functional Ni-Fe/Si 3 N 4 -TiN nanocomposite coatings were electro-codeposited from sulphamate-N,N-dimethylformamide bath containing dispersed Si 3 N 4 and TiN nano-particles 10 g/L each. The effect of current density on the incorporation of the ceramic particulate and on the properties of the deposits was investigated. The deposited coatings were characterized using various advanced techniques such as scanning electron microscopy, X-ray diffractometry, transmission electron microscopy and atomic force microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The incorporation of nano-sized particles is in uenced by various process parameters, including particle concentration, shape, size, bath composition, additives, pH, and current density. Researchers suggested that the applied current density, particle type, particle concentration, and bath agitation are the main in uencing factors in the co-deposition process [5,6]. The aim of the present work is the production of Cu-Co/WC nanocomposite coating using copper sulfate bath and also speci cation of optimum processing condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of nano-sized particles is in uenced by various process parameters, including particle concentration, shape, size, bath composition, additives, pH, and current density. Researchers suggested that the applied current density, particle type, particle concentration, and bath agitation are the main in uencing factors in the co-deposition process [5,6]. The aim of the present work is the production of Cu-Co/WC nanocomposite coating using copper sulfate bath and also speci cation of optimum processing condition.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical deposition has a widespread use in nanotechnology since it can be used to ll three-dimensional features at room temperature with good control of thickness and morphology [1]. During the last few decades, researchers have attempted to improve the properties through electrocodeposition of hard particles such as WC, Al 2 O 3 , SiC, and Si 3 N 4 [2][3][4][5] in various metal matrix materials such as Ni and Cu [2,3]. The copper electroplates are widely used in engineering applications due to their high electrical and thermal conductivity, proper ductility, and required corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Ni-Fe alloys, specially nanocrystalline permalloy (80% Ni-20% Fe) have always been of prime importance in industry and technology especially when requiring strong mechanical strength, corrosion resistance, good electrical conductivity, special optical properties and a soft magnetic nature [11][12][13][14][15]. Usually the arithmetic roughness of Ni-Fe alloy surfaces is found to be very high which should be as low as possible for aerodynamic surfaces (for example in wind turbine or on aircraft).…”
Section: Introductionmentioning
confidence: 99%
“…15 Although oxide ceramic particle reinforced metal matrix composites have been extensively studied due to their high hardness, wear and corrosion resistance, to the best of our knowledge no comprehensive report is available that includes benefits from two or more oxide ceramic parz E-mail: vijaybs@bhu.ac.in ticles in the Ni-Fe alloy matrix. Interesting results of our previous investigation 16 with mixed nitride ceramic particles in the Ni-Fe alloy matrix encouraged us to extend our study with mixed oxide ceramic particles, particularly, in near permalloy matrix because the permalloy has special position among the Ni-Fe alloys.…”
mentioning
confidence: 93%